Environmental factors affect swing gates as a barrier to large carnivores entering game farms. (23rd December 2014) - Rust, Niki A.; Nghikembua, Matti T.; Kasser, Joel J. W.; Marker, Laurie L.
Abstract Burrowing animals such as warthog (Phacochoerus africanus), Cape porcupine (Hystrix africaeaustralis) and aardvark (Orycteropus afer) are able to compromise the integrity of fenced‐in farmlands by digging holes under game fences. These holes provide access for predators to enter the farm where they can kill livestock or captive game animals. Data collected from the use of swing gates (n = 263) installed along a 23.93 km game fence in the Otjozondjupa region of Namibia was analysed to determine the factors that influenced their efficacy at reducing hole creation along the fence by digging animals. Statistical analyses revealed that soil substrate, grass height, vegetation density, distance to the nearest permanent water source and season influenced digging activity along the fence line. The number of holes created and reopened decreased over time from the start of the study period, probably demonstrating that burrowing animals had learnt to use the swing gates rather than dig holes under the fence. These factors can inform the correct future usage of swing gates as a large predator exclusion method to ensure that they do not enter game farms, which will reduce the need to lethally control carnivores and burrowing animals.